Reproductive interactions between fugitive farmed and wild Atlantic cod (Gadus morhua) in the field - Meager, J J; Skjaeraasen, J E; Ferno, A; Lokkeborg, S (Canadian Journal of Fisheries and Aquatic Sciences, 2010)
Atlantic cod (Gadus morhua) are being increasingly farmed in net pens adjacent to coastal populations that are currently at historic lows. One concern is that farmed escapees enter local spawning shoals and mate with wild cod. We tested for the potential of escaped farmed cod to interact and hybridize with wild fish by examining the spatial dynamics of, and associations between, fish tagged with ultrasonic transmitters. Based on these data, we also investigated the basic mating system of cod in the field. The spawning ground was best described as a lekking arena. Wild males aggregated near the seafloor and associations between individuals were frequent. Wild females had a pelagic and dispersed distribution and rarely associated with each other. Associations between individual wild males and females were also infrequent. Farmed males rarely associated with wild fish and had core usage areas above the wild males, suggesting that they were not admitted into the spawning arena. Farmed females were over the spawning arena more frequently than wild females and often associated with wild males at the depth of the spawning arena, indicating potential mating with wild males and the possibility of courtship interference. Hence, hybridization between escaped farmed and wild cod is likely.